Answer:
The standard form of the equation is
[tex]{(x - 1)}^{2} + {(y - 0)}^{2} = {3}^{2} [/tex]
Step-by-step explanation:
The given circle has equation:
[tex] {x}^{2} + {y}^{2} - 2x - 8 = 0[/tex]
We regroup similar terms to obtain:
[tex] {x}^{2} -2x + {y}^{2} = 8[/tex]
We now complete the square to obtain:
[tex] {x}^{2} -2x + {( - 1)}^{2} + {y}^{2} = 8 + {( - 1)}^{2} [/tex]
[tex] {(x - 1)}^{2} + {(y - 0)}^{2} = 9 [/tex]
Or
[tex]{(x - 1)}^{2} + {(y - 0)}^{2} = {3}^{2} [/tex]
This is now of the form:
[tex]{(x - h)}^{2} + {(y - k)}^{2} = {r}^{2} [/tex]
which is referred to as the standard form equation of the circle: